THE EFFECT OF HIGH INTENSITY INTERVAL TRAINING AND BODY MASS INDEX EXERCISE ON REDUCING BODY FAT FOLD LEVELS - Moch. Saiful Amri Al-khusaini; Said Junaidi; Ipang Setiawan (Journal of Physical Education and Sports, 2024)
The aim of this research is to analyze 1). The effect of HIIT training with a 2:1 ratio on reducing body fat folds, 2). The effect of HIIT training with a ratio of 1:3 on reducing body fat folds, 3). The difference between HIIT training ratios of 2:1 and 1:3 in reducing body fat folds, 4). Differences in decrease in body fat folds between overweight and obese BMI. This research uses a quasi-experimental method, a 2 x 2 factorial research design. The test instrument in this research is 1). Body fat thickness test, 2). Body Mass Index (BMI). Data analysis using Two Way Anova. The research results show: 1). HIIT training with a ratio of 2:1 to a decrease in body fat folds obtained a significance value of 0.01 < 0.005, 2). HIIT training with a ratio of 1:3 to a decrease in body fat folds obtained a significance value of 0.04 < 0.005, 3). HIIT training with a ratio of 2:1 and 1:3 to reduce body fat folds obtained a significance value of 0.02 < 0.005, 4). BMI overweight and obesity on decreasing body fat folds obtained a significance value of 0.00 <0.005.